"Tradition", person, gender, and STD/HIV/AIDS in southern Mozambique "Tradição", pessoa, gênero e DST/HIV/AIDS no Sul de Moçambique - Luiz Henrique Passador (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2009)
In southern Mozambique, the "traditional" notion of personhood is constructed through a process, as an outcome of diachronic and synchronic social relations that encompass kin and other peers, including spirits. Both person and body are thought of as elements traversed and determined by these relations, which include the gender relations whose complementarity finds expression in alliances and the production of descendants. In this system of agnatic kinship, descent is possible through women, who produce the male and female persons. Because of women's structural position, they may be suspected of fostering deconstruction of the person as well, with diseases providing the objective data that ground such a charge. To a certain degree, HIV/AIDS has been experienced in terms of this sociocultural arrangement, which defines disease as the result of action by social subjects that jeopardizes the person, placing women in the vulnerable position of being seen as the producers of disease. This has defined the ways in which people experience both the epidemic as well as STD/HIV/AIDS prevention and treatment messages and public policies. No Sul de Moçambique, a noção "tradicional" de pessoa constrói-se numa perspectiva processual, como fluxo de relações sociais diacrônicas e sincrônicas que congregam parentes e outros pares, inclusive os espíritos. Pessoa e corpo são pensados como elementos atravessados e determinados por essas relações, que congregam as relações de gênero em termos de complementaridade realizada nas alianças e produção da descendência. Num sistema de descendência local, é através das mulheres que a filiação e a descendência são possíveis, gerando a pessoa masculina e feminina. Essa posição estrutural as coloca sob suspeitas de promoção da desconstrução da pessoa, sendo as doenças percebidas como dados objetivos que apontam para tal ação. Em certa medida, o HIV/AIDS tem sido experimentado nos termos dessa disposição sócio-cultural que define as doenças como ações de sujeitos sociais que colocam em risco a pessoa, construindo uma situação de vulnerabilidade das mulheres ao estabelecê-las como promotoras de doenças. Tal cenário tem determinado as experiências que os sujeitos têm com a epidemia e com os discursos e políticas públicas de prevenção e tratamento das DST e HIV/AIDS.